Black power, Jewish politics : reinventing the alliance in the 1960s - Dollinger, Marc, 1964- (Brandeis series in American Jewish history, culture, and life., 2018)
"Explores how American Jews leveraged the Black Power movement to strengthen American Jewish religious, ethnic, and cultural life"--Provided by the publisher.